Electrical Characteristics of Aluminum Air Battery Under Open-Circuit And Closed-Circuit Conditions - Cheah, Zhen Ke (2020)
Aluminium-air battery has great potential as it is capable of achieving high theoretical energy density of 8100 Wh kg-1 , and high theoretical cell voltage of 2.7 V. However, the aluminium anode is vulnerable to self-corrosion and surface passivation issues, causing the practical aluminium-air battery to yield energy density at only 1300 Wh kg-1 . The practical cell voltage ranges from 1.22 V – 1.46 V for aluminium-air battery in 4M NaOH electrolyte. Therefore, the open-circuit condition such as self-corrosion, surface passivation behaviours, and open-circuit voltage are studied. The closed-circuit condition that includes discharge characteristics is investigated. This research is to study the selfcorrosion and surface passivation behaviours of pure aluminium and alloy 6063 in alkaline electrolyte using SEM-EDX, XRD analysis, and their corresponding open-circuit voltage using potentiostat. Besides that, the effects of graphite felt and graphite powder as catalysts on the discharge characteristic of aluminiumair battery is investigated using potentiostat. The electrolyte for the aluminiumair battery is 4M KOH solution. It is found that alloy 6063 as anode has better electrical characteristics that can achieve 10.3% higher open-circuit voltage, better discharge characteristics on average, and 54 % better capacity as compared to pure aluminium. However, the self-corrosion in alloy 6063 is 60 % faster than pure aluminium based on Tafel plot. The graphite felt is a better catalyst than graphite powder, it has significantly improved the initial discharge voltage by 35 % and 41 %, as well as the final discharge voltage by 65 % and 69 % for pure aluminium and alloy 6063 respectively.